Class 3 semaphorins negatively regulate dermal lymphatic network formation - Uchida, Yutaka (Biol Open, 2015)
The development of a patterned lymphatic vascular network is essential for proper lymphatic functions during organ development and homeostasis. Here we report that class 3 semaphorins (SEMA3s), SEMA3F and SEMA3G negatively regulate lymphatic endothelial cell (LEC) growth and sprouting to control dermal lymphatic network formation. Neuropilin2 (NRP2) functions as a receptor for SEMA3F and SEMA3G, as well as vascular endothelial growth factor C (VEGFC). In culture, Both SEMA3F and SEMA3G inhibit VEGFC-mediated sprouting and proliferation of human dermal LECs. In the developing mouse skin, Sema3f is expressed in the epidermis and Sema3g expression is restricted to arteries, whereas their receptor Nrp2 is preferentially expressed by lymphatic vessels. Both Sema3f;Sema3g double mutants and Nrp2 mutants exhibit increased LEC growth in the skin. In contrast, Sema3f;Sema3g double mutants display increased lymphatic branching, while Nrp2 mutants exhibit reduced lymphatic branching. A targeted mutation in PlexinA1 or PlexinA2, signal transducers forming a receptor complex with NRP2 for SEMA3s, exhibits an increase in LEC growth and lymphatic branching as observed in Sema3f;Sema3g double mutants. Our results provide the first evidence that SEMA3F and SEMA3G function as a negative regulator for dermal lymphangiogenesis in vivo. The reciprocal phenotype in lymphatic branching between Sema3f;Sema3g double mutants and Nrp2 mutants suggest a complex NRP2 function that regulates LEC behavior both positively and negatively, through a binding with VEGFC or SEMA3s.